Determinants of Preterm Birth among Women Who Gave Birth in Amhara Region Referral Hospitals, Northern Ethiopia, 2018: Institutional Based Case Control Study - Abebayehu Melesew Mekuriyaw; Muhabaw Shumye Mihret; Ayenew Engida Yismaw (International Journal of Pediatrics)
Background. Preterm birth refers to a birth of a baby before 37 completed weeks of gestation and after fetal viability. It is now the leading cause of new born deaths. Although identifying its common risk factors is mandatory to decrease preterm birth and thereby neonatal deaths, there was a dearth of studies in the study area. Objective. The aim of this study was to identify determinants of preterm birth among women who gave birth in Amhara region referral hospitals, Northwest Ethiopia, 2018. Method. An institutional based case-control study was conducted from September 01 to December 01/2018. A total of 405 mothers (135 cases and 270 controls) were included in the study. Multistage sampling technique was employed. Data were collected using structured questionnaire through face to face interview and checklist via Chart review. Data were entered into Epi Info version 7 and export to Statistical Package for Social Sciences (SPSS) version 20 for analysis. Descriptive statics like mean, frequency and percentage was used to describe the characteristics of participants. Both bivariable and multivariable analyses were carried out. Variable having    p-value <0.05 in binary logistic regression were the candidate for multivariable analyses. Finally, the statistical significance of the study was claimed based on the Adjusted Odds Ratio (AOR) with 95% Confidence Interval (CI) and its p-value <0.05. Result. The result of multivariable analysis show that mothers with no formal education (AOR = 2.24; 95% CI: 1.28, 3.91), history of abortion (AOR = 2.92; 95% CI: 1.3, 6.4), multiple gestation (AOR = 4.1; 95% CI: 1.7, 9.8), hemoglobin level <11 gm/dl (AOR = 2.75; 95% CI: 1.11, 7.31), premature rupture of membrane (AOR = 6.4; 95% CI: 3.23, 12.7) and pregnancy induced hypertension (AOR = 4.74; 95% CI: 2.49, 9.0) had statistically significant association with experiencing preterm birth. Conclusion and Recommendation. Most of the determinants of preterm birth found to be modifiable. Thus, putting emphasis for prevention of obstetric and gynecologic complications such as anemia, premature rupture of membrane and abortion would decrease the incidence of preterm birth. Moreover, strengthening Information Communication Education about prevention of preterm birth was recommended.